Impact of the variability of presentation ways of stimuli and their associated sign-language explanation in educational computer programs on academic achievement of the English language among Deaf High school students - Saati, Adnan Abdulhamid (Journal of Educational and Psychological Sciences, 2020)
This research aims at exposing the impact of the variability of presentation ways of visual stimuli and their associated sign-language explanation(visual stimuli without sign-language explanation/ visual stimuli followed by sign-language explanation/ visual stimuli simultaneous with the presentation of sign-language explanation) in educational computer programs on academic achievement of some English words among high school students (deaf group) in the integration program At Ain Jaloot Secondary School and the integration program in Dumah Al Jandal Secondary School.The study population included students of the integration program of the two schools, the sample size was determined and it included (36) deaf students who were randomly distributed into three pilot groups.The prior assessment was applied by using the electronic achievement test prepared by the Quiz Creator application, its reliability and validity were then confirmed by checking the coherence of the three groups.The three pilot groups enrolled for an educational computer program, in which the first group studied the impact of the variability of visual stimuli without sign-language explanation, the second group studied the visual stimuli followed by sign-language explanation, then the third group studied the visual stimuli simultaneous with the presentation of sign-language explanation the groups and each group of the three groups included a sample of 12 deaf students.The results of the study showed:Presence of differences which are statically significant (P value= 0.05) between the average degrees of the three groups in favor of the second group who studied the visual stimuli followed by a sign-language explanation.
Keywords: Electronic learning; e-learning; Educational computer programs; Academic achievement; English Language; Deaf